New aryl Schiff bases of thiadiazole derivative of ibuprofen as DNA binders and potential anticancer drug candidates. Issue 10 (3rd July 2021) - Farooqi, Shahid Iqbal; Arshad, Nasima; Channar, Pervaiz Ali; Perveen, Fouzia; Saeed, Aamer; Larik, Fayaz Ali; Javed, Aneela; Yamin, Maham
Abstract: The work presented in this paper describes the synthesis of two new aryl Schiff bases [( E )- N -(4-(benzyloxy)-3-methoxybenzylidene)-5-(1-(4-isobutylphenyl)ethyl)-1, 3, 4-thiadiazol-2-amine] (ASB-1) and [( E )- N -(4-(benzyloxy)benzylidene)-5-(1-(4-isobutylphenyl)ethyl)-1, 3, 4-thiadiazol-2-amine] (ASB-2). These compounds were characterized by different analytical techniques and then studied for DNA binding. Binding studies were carried out at neutral pH (7.0) and at 37 °C by theoretical and experimental methods including DFT, molecular docking, spectroscopy (UV-visible, fluorescence), cyclic voltammetry (CV) and viscometry. Further investigations of these compounds were done on hepatocellular carcinoma; Huh-7 cancer cell line. Binding constant, free energy change and binding site size, i.e. Kb, ΔG and n were evaluated which indicated that both ASB-1 and ASB-2 bind significantly and spontaneously with the DNA. However, data revealed relatively greater binding of ASB-1 with DNA. Spectral and voltammetric results were found supportive of each other. Binding site sizes and viscosity measurements verified the mixed binding mode of interactions as observed in molecular docking analysis, i.e. intercalation with groove binding. DNA binding studies were very well correlated with the in-vitro studies performed on Huh-7 cell line as well as normal HEK-293 cell lines. The compound ASB-1 not only showed greater binding affinity toward DNA but also showed greater anticancer potency with least IC50 value as compared to ASB-2. Graphical Abstract: Highlights: New aryl Schiff bases of thiadiazole derivative of ibuprofen ASB-1 and ASB-2 Reactivity and mixed binding mode of interaction with DNA by DFT and docking Good agreements in the binding parameters by spectroscopy and voltammetry Kb, ΔG and n determined greater for ASB-1indicating its stronger binding with DNA Greater anticancer potential of ASB-1against Huh-7 cell line Communicated by Ramaswamy H. Sarma